Gender, food security and AIDS in internally displaced people’s camps in Uganda: Implications for HIV responsive policy and programming - Bukuluki, Paul; Mugumya, Firminus; Neema, Stella; Kafuko, Agatha; Ochen, Eric Awich (International Food Policy Research Institute, 2008)
Food and nutritional insecurity coexists with high HIV prevalence rates in war-affected communities in the north and northeastern regions of Uganda. Women and especially female children are disproportionately affected. Gender relations underpin the interaction between AIDS and food insecurity, though there is limited documentation on the influence of conflict and displacement on gender relations and how they may exacerbate household food insecurity and risk of HIV infection. There is also limited understanding of the extent to which Uganda’s current policies and programs address the complex issues involved in gender, HIV, and food insecurity in IDP camps.